Assessment of Tourism Features’ Deficiencies and Tourist Demand of Destinations in the Niger Delta, Nigeria - Ideh, Eric; Awaritefe, O.D.; Sajini, F. I. (Universitas Indonesia Mandiri, 2025)
Tourism is important for the growth and development of any economy, either national or regional; thus, it is essential to pay attention to the factors that motivate tourist demand for a destination. In the Niger Delta, policies on tourism are not well articulated, and one of the consequences of this is that the recreational needs of both local and foreign tourists are not adequately met. In light of the foregoing, this study sought to investigate tourism features deficiencies and the tourist level of demand for the destination in the Niger Delta, Nigeria. The Service Quality Theory (SQT) was the theoretical framework that guided the study. Twelve tourist destinations were chosen from six states that comprise south-south Niger Delta, including Ossosso and Igarra tourist destinations in Edo State, Rivotel hotel and Gordon Resort hotel in Delta State, Ox-Bow lake and Peace Park tourist destinations in Bayelsa State, Port Harcourt Zoo and Pleasure Park in Rivers State. Ibeno Beach and Garden Hotel Resort in Akwa-Ibom state, as well as the National Museum and Tinapa tourist destination in Cross River State. A total of 950 respondents across the 12 tourist destinations constituted the sample size for this study, and primary data through the use of well-structured questionnaires were extracted from these respondents. The Crumbach Alpha method was used to measure the validity of the instrument, and result shows a strong positive reliability of the instrument. The data was analyzed first by using descriptive statistics, while the multiple Regression technique was used to test the study hypothesis. The findings of the study revealed that there is a significant difference among tourist destinations in their deficiency of tourism features. The findings also revealed that features which were lacking in tourist destinations but needed urgent provisions are a variety of affordable food and drinks, horse and donkey riding, a standard zoo and museum, and affordable and comfortable accommodation. Others include: student hostels, picnics, attractions and medical facilities. In light of these findings, the study recommended, among others, that tourist facilities, considered lacking, should be adequately provided and tailored to cater for the diverse needs of tourists in destination centers in the Niger Delta.